PENGEMBANGAN INSTRUMEN PENILAIAN KEMAMPUAN MENARI PADA PESERTA DIDIK SMA NEGERI 3 WATANSOPPENG KABUPATEN SOPPENG - Rosnawati, Rosnawati (Universitas Negeri Makassar, 2017)
This research aims at developing dancing assessment instrument of students at SMAN 3 Watansoppeng based on theoretic and empirical aspects. The kind of this research is research and development. The subjects were teacher and students of class X at SMAN 3 Watansoppeng in Soppeng district. The research was conducted in SMAN 3 Watansoppeng in Soppeng district. Data was collected by employing rubric test instruments. Data was analyzed by employing descriptive quantitative analysis. The result of the study reveals that theoretically, the result of dancing assessment instrument of student at SMAN 3 Watansoppeng is valid in terms of content through 3 dimensions, namely body work, performance, and choreography. Those there dimensions cover 12 indicators. The body work dimension consists of flexibility, balance, agility, and endurance. The carriage dimension consists of moving technique, rhythm, compactness, and inspirations. The choreography dimension consists of shape, atmosphere, accompaniment, and makeup. Empirically, the result of dancing assessment instrument of student at SMAN 3 Watansoppeng is confirmed as valid through field test and reliable based on intra-rater approach.